1991
DOI: 10.1136/gut.32.3.246
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for hypomotility in non-ulcer dyspepsia: a prospective multifactorial study.

Abstract: A prospective multifactorial study of symptoms and disturbance of gastrointestinal function has been undertaken in 50 patients with non-ulcer dyspepsia. Objective tests including solid meal gastric emptying studies, gastric acid secretion, E-HIDA scintiscan for enterogastric bile reflux, and hydrogen breath studies were carried out in all patients and validated against control data. Gastroscopy and biopsy were carried out in non-ulcer dyspepsia patients only. Non-ulcer dyspepsia patients were categorised on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(44 citation statements)
references
References 26 publications
1
41
1
1
Order By: Relevance
“…W czasie włączania do badania oraz 2 tyg. po skutecznej eradykacji wypełniali oni kwestionariusz mający na celu określe-nie nasilenia objawów dyspeptycznych oraz zostali poddani pomiarowi GE z posiłku stałego o wartości energetycznej 378 kcal z dodatkiem 75 μl 13 C-kwasu oktanowego. Wartości normatywne kinetyki GE wyznaczono u 12 zdrowych osób.…”
Section: Streszczenieunclassified
See 2 more Smart Citations
“…W czasie włączania do badania oraz 2 tyg. po skutecznej eradykacji wypełniali oni kwestionariusz mający na celu określe-nie nasilenia objawów dyspeptycznych oraz zostali poddani pomiarowi GE z posiłku stałego o wartości energetycznej 378 kcal z dodatkiem 75 μl 13 C-kwasu oktanowego. Wartości normatywne kinetyki GE wyznaczono u 12 zdrowych osób.…”
Section: Streszczenieunclassified
“…Using algorithms of non-linear regression implemented in the Statistica 6.1 software [12], the curves of momentary 13 C recovery within the exhaled air were fitted to the function:…”
Section: Measurement Of 13 Co 2 and Derivation Of Gastric Emptying Pamentioning
confidence: 99%
See 1 more Smart Citation
“…The role of Helicobacter pylori infection has been controversial but more recent studies have revealed small benefit from H. pylori eradication. Gastric sensorimotor abnormalities have been extensively investigated in patients with FD and delayed gastric emptying has been considered the most important mechanism since an abnormal gastric emptying was observed in 20 to 50% of patients with FD (3,4), but the relationship between abnormalities of gastric emptying and symptoms is unclear. Impaired gastric accommodation to a meal has been demonstrated in patients with FD by studies on the gastric barostat, causing an abnormal intragastric distribution of food.…”
Section: Introductionmentioning
confidence: 99%
“…Some genetic factors such as polymorphism or psychosocial factors or some other factors regarding bacterial flora are likely responsible for pathogenesis (2,5). Most of the patients with dyspeptic complaints of unknown cause were found to have various gastric and duodenal motility abnormalities leading to antral hypomotility (6,7), gastric motor abnormalities due to abnormal gastric myoelectrical activity, and delayed gastric emptying (8).…”
Section: Introductionmentioning
confidence: 99%